Hijab dan Jilbab Dalam Pandangan Haji Agus Salim (Sekolah Tinggi Agama Islam Negeri (STAIN) Teungku Dirundeng Meulaboh Aceh Barat, 2017)
In practice the principles of the religion, problems of the women’s awrah is often in public conversation because it’s one of the practice teachings of Islam. Actually the issue is not something new. However, the issue arises when a muslims want to practice Islam in pure. Haji Agus Salim as a muslim scholar, has expressed to his thoughts about women. Problems of veils gets his attention specifically. Therefore, this paper will discuss the view of Haji Agus Salim about Veils